“TikTokers” Teacher In The Code Of Ethic For Teacher In Islamic Education - Lindra, Afni; Aprison, Wedra; Asi, Redha Septia (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2024)
In the digital era, teachers are not only educators in schools but can also work as TikTokers in the TikTok application or cyberspace. The success of TikTokers in earning a lot of money by creating various kinds of content has motivated teachers to become content creators. However, not all teachers are wise and careful when choosing content topics. Moreover, the content created by teachers is easily accessible to many people, including their students. The diverse range of content produced by teachers on the TikTok application can have an impact on the knowledge and character development of students and society as a whole. This is because the TikTok application is currently popular among people of all age groups, including children, teenagers, adults, and the elderly. Upon examining the content created by teachers, it is evident that some teachers are appropriate, careful, and wise in their content creation, while others are not. Therefore, this discussion aims to explore the phenomenon of teachers as TikTokers from the perspective of Islamic education, focusing on teachers' creative activities in cyberspace through the TikTok application. This research adopts a descriptive qualitative method, utilizing library research. Keywords: Teacher, Tiktokers, Islamic Education